Factors contributing to the increase of covid-19-infected patients in different families in Latin America - Junchaya Yllescas , Vilma Amparo (2021)
Objective: To evaluate the factors that contribute to the increase of patients infected by COVID-19 in different families in Latin America. Material and  methods:  Being a cross-sectional descriptive study. The population consisted of users of social networks with respect to factors contributing to COVID-19 infection. A digital questionnaire was used with sociodemographic variables, biosecurity factors, cultural factors and environmental factors. Descriptive and bivariate analysis was performed according to the nature of the variables. Results:1123 questionnaires of Facebook users from Latin America were analyzed, including: Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Paraguay, Uruguay, Venezuela and Peru, most of them women (77 %), (81 %) between 18 and 31 years old.  About the biosecurity factors that contribute to the contagion of the population, 43% of the respondents indicated that it is due to not using masks and face shields, as well as cultural factors, 55% indicated that it is not interested in respecting norms, as environmental factors, 74% considered that environmental pollution has to do with the increase, another 59% responded that the population of urban housing areas is the most infected and 49% said that the air is the polluting element that contributes to the contagion of COVID-19. Conclusions:  Facebook users consider that Latin American inhabitants are infected by not complying with biosecurity factors, cultural factors, and various environmental factors, whose conditions that many people live in make them even more vulnerable and more dangerous.